Cytosolic zinc accumulation contributes to excitotoxic oligodendroglial death. Issue 5 (26th February 2013) - Mato, Susana; Sánchez‐Gómez, María Victoria; Bernal‐Chico, Ana; Matute, Carlos
<x xml:space="preserve">Abstract</x> Dyshomeostasis of cytosolic Zn2+ is a critical mediator of neuronal damage during excitotoxicity. However, the role of this cation in oligodendrocyte pathophysiology is not well understood. The current study examined the contribution of Zn2+ deregulation to oligodendrocyte injury mediated by AMPA receptors. Oligodendrocytes loaded with the Zn2+‐selective indicator FluoZin‐3 responded to mild stimulation of AMPA receptors with fast cytosolic Zn2+ rises that resulted from intracellular release, as they were not blocked by the extracellular Zn2+ chelator Ca‐EDTA. Pharmacological experiments suggested that AMPA‐induced Zn2+ mobilization depends on cytosolic Ca2+ accumulation, arises from mitochondria and protein‐bound pools, and is triggered by mechanisms that do not involve the generation of reactive oxygen species. Moreover, intracellular Zn2+ rises resulting from AMPA receptor activation seem to be promoted by Ca2+‐dependent cytosolic acidification. Addition of the cell‐permeable Zn2+ chelator TPEN significantly reduced mitochondrial membrane depolarization, reactive oxygen species production, and cell death by sub‐maximal activation of AMPA receptors both in vitro and in situ, suggesting that Zn2+ deregulation is an important mediator of oligodendrocyte excitotoxicity. These data provide evidence that strategies aimed at maintaining Zn2+ homeostasis may be useful for the treatment of disorders in which excitotoxicity is an important trigger of oligodendroglial death.